Comparison between twin block appliance and mandibular advancement on clear aligners in the improvement of airway dimension: incremental versus maximum bite advancement - Cretella Lombardo, Elisabetta; Lugli, Letizia; Cozza, Paola; Lione, Roberta; Loberto, Saveria; Pavoni, Chiara (Frontiers in Oral Health, 2024)
ObjectiveThe aim of the present retrospective study was to compare the changes resulting from treatment using the MA and the TB with special regard to the oro-and naso-pharyngeal sagittal airway dimensions in subjects with dentoskeletal Class II malocclusions and positive history of Sleep Disorder Breathing (SDB) diagnosed through the Pediatric Sleep Questionnaire (PSQ).Materials and methodsThis retrospective study involved 2 groups of subjects: patients treated with Twin Block (TB group: n = 22, 10 males, 12 females; mean age 12.0 ± 1.3 years) and patients treated with Mandibular Advancement (MA group: n = 23, 11 males, 12 females; mean age 12.2 ± 1.1 years). Pretreatment (T1) and posttreatment (T2) lateral cephalograms were analyzed. All patients underwent the PSQ to diagnose SDB.ResultsIn both treated groups there was an increase in the airways dimensions and an improvement in symptoms related SDB. The statistical comparison of the changes between T1 and T2 in the TB group showed a significant increment in upper airway size (PNS-AD2, +1.50 mm + −3.30; McNamara's upper pharynx dimension, +2.21 + −4.21) after active treatment. The MA group showed similar results during active treatment with a significant increase in both upper (PNS-AD2, +2.72 + −2.65; McNamara's upper pharynx dimension, +2.97 + −3.07) and lower (PNS-AD1, +2.17 mm + −3.54) airway size.ConclusionsDespite the different structure of these two devices and the different advancement protocols, both appliances were valuable as a suitable treatment option for Class II patients with respiratory disorders, inducing an increase of upper and lower airway size and a significant reduction in diurnal symptoms.